Inkjet Printed Energy Storage Systems for Electrochemical Testing and In-Situ TEM Analysis - MCKEON, LORCAN (Trinity College Dublin. School of Physics. Discipline of Physics, 2019)
Understanding of how materials store charge in supercapacitor and battery systems is fundamental to improving these classes of energy storage devices. While materials can be analysed and examined before they are incorporated into a device and again after they have been cycled, this leaves a large gap in the intervening period during which many assumptions about the function of the device must be made. In-situ TEM analysis of materials is a technique that could allow for the accurate imaging of materials in this intervening stage, directly visualising the chemical and physical changes that occur in supercapacitor and battery electrodes as they charge and discharge. In this work, a robust, rapid and accurate method of fabricating microelectrodes for in-situ TEM study is presented. Inkjet printing is used to deposit discrete lines of material from solution processed nanomaterial inks. The characteristic coffee staining effect that is observed in the patterns produced by drying droplets is utilised to deposit narrow paths of material along a pre-fabricated metallic electrode. These lines can be reliably printed repeatably with ≈10 μm accuracy. Initial in situ tests were conducted with a single MnO 2 -graphene electrode, which stores charge in a pseudocapacitive manner. When this electrode was immersed in aqueous electrolyte, and cycled with typical MnO 2 cycling parameters, dendritic formations were observed through the liquid growing outwards from the electrode edge. Following on from these initial tests, Si nanoparticles, a battery anode which displays a large volumetric change during its lithiation process, were then deposited. These electrodes were deposited in the same manner, utilising inkjet printing, along with a counter electrode of LiFePO 4 . The particles were observed during their cycling process through STEM imaging, successfully resolving individual nanoparticles at the metallic electrode edge through the liquid electrolyte layer. Due to electrolyte beam degradation, an electrolyte study was conducted, settling on a 0.1 M LiClO 4 in EC:DMC as an appropriate electrolyte for long term study. The final section of the work sought to utilise the same methods of deposition and the same methods of ink synthesis, Liquid Phase Exfoliation, to fabricate larger scale flexible devices. A MXene material, Ti 2 C 3 T X in a variety of organic solvents was used as a base printing ink. Using these inks, planar supercapacitors were printed onto a flexible coated PET substrate. No further treatment of fabrication processes were required after the initial printing, apart from the drop casting of gel electrolytes. These devices showed excellent charge storage ability, with the NMP based ink printed to 25 print passes displaying an areal capacitance of 12mF cm -2 and the onset of resistive behaviour was not observed until a scan rate of 500 mV s 1 was reached. These devices were then integrated into larger systems, with devices printed in both series and parallel showing higher voltage capabilities and current responses respectively. In summary, this work intends to show inkjet printing as robust deposition platform, capable of creating micron accurate TEM samples, and using the same materials and techniques, larger scale flexible integrated circuitry. This allows for the same materials to be used in both processes allowing for a full characterisation of the material on a nanoscale, which can then be deposited into a working device.
APPROVED
Keywords: Inkjet printing; Supercapacitors; 2D Materials; TEM; In-situ electrochemistry